Upminimal Algebras of Binary Operations of Rank 3 - Eremenko, Dmitry (Computer Tools in Education, 2021)
The work is devoted to the study of the lattice of algebras of binary operations of rank 3 and finding the upminimal algebras of binary operations of rank 3. Upminimal algebras were divided into two classes: reducible algebras and irreducible algebras. The property of operations generating irreducible upminimal algebras was obtained. The use of this property made it possible to find all irreducible algebras of binary operations of rank 3. To search for reducible algebras, we used the previously obtained results on minimal algebras of binary operations of rank 3. The results of the work are presented in tabular form.